Business groups in agriculture. Impact of ownership structures on performance: The case of Russia's agroholdings - Andriy Matyukha (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2017)
[Objective and hypotheses] Due to the absence of legal and structural backings with neither an existing law clearly identifying the phenomena, nor publically available transparent consolidated financial reporting within the integrated structures in Russia's agricultural sector, it is a widely accepted fact that even qualitative data, portraying the picture of the agroholding subsidiaries and/or affiliates, are scarce, e.g. WANDEL (2011). Notwithstanding the previous research challenges, the current study fills in the existing gaps in the literature on integrated agro-food formations in Transition Economies and contributes to the prominent research pertaining to integrated structures in the Russian Federation, thus far, e.g. KHRAMOVA (2003), KOESTER (2005), HOCKMANN et al. (2007), SEROVA (2007), DMITRI RYLKO (2010), WANDEL (2011), UZUN et al. (2012). In effort to contribute to filling the existing gaps in literature to scholarship interested in Corporate Governance of Business Groups in the agricultural complex, on the basis of the Russian Federation, the principal aims of this dissertation are twofold: 1. A comparative analysis of ownership structures impact on performance of agroholding member farms and independent farms. 2. A comprehensive depiction of ownership structures of agroholdings in Russia. Literature suggests the production costs to be best mediated by independent "family farms", e.g. (BINSWANGER et al., 1995), (EASTWOOD et al., 2010), (POLLAK, 1985). In addition, Russian Federation has long been notorious for its corrupt socioeconomic environment and high corporate taxation, e.g. (KPMG, 2006). Consequently, the following hypotheses were henceforth developed in this study: 1. Agroholding membership is negatively related to farm performance. 2. Private ownership positively influences farm performance. These hypotheses are based on the fact that most of Russia's corporate private affiliates are registered in foreign "tax-heaven" zones, such as Cyprus. Similarly, given legal and "blat" (political) connections, participation of the state in farm ownership is also assumed to also exert a positive impact on farm performance. This work opens the door to scholarship interested in the Corporate Governance of Russian agricultural complex and, henceforth, uncovers some of the major agroholdings existing in the Russian Federation since 1995 until present. Two detailed ownership-performance relationship analyses at aggregate agroholding and independent farm levels are revealed, followed by the corporate ownership structures depiction in case studies. The case studies depict agroholdings' regional dissemination, performance magnitude, and strategic importance for the Russian Federation.
urn:nbn:de:gbv:3:2-71327
Keywords: 330